2010
DOI: 10.3168/jds.2010-3086
|View full text |Cite
|
Sign up to set email alerts
|

The effect of selenium supplementation before calving on early-lactation udder health in pastured dairy heifers

Abstract: Selenium (Se) deficiency has been associated with lowered resistance to mastitis in dairy cattle. However, little published data exists on the effect of Se supplementation before calving on udder health of pastured dairy heifers. Further, the relative efficacy of injectable barium selenate and oral organic Se for improving udder health in cows has not previously been tested. The objectives of this study were to determine the effects of precalving Se supplementation and type of supplementation on the blood acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…More recent studies confirmed that higher bulk tank Se concentrations were associated with a lower risk of being a Staphylococcus aureus -positive herd [45]. Moreover, Se supplementation of pastured dairy heifers and cows before calving reduced the prevalence of new intramammary infections and high SCC during early lactation [46, 47]. Se nutritional status is important to many reproductive functions of dairy cattle as well.…”
Section: Se and Dairy Cattle Healthmentioning
confidence: 98%
See 1 more Smart Citation
“…More recent studies confirmed that higher bulk tank Se concentrations were associated with a lower risk of being a Staphylococcus aureus -positive herd [45]. Moreover, Se supplementation of pastured dairy heifers and cows before calving reduced the prevalence of new intramammary infections and high SCC during early lactation [46, 47]. Se nutritional status is important to many reproductive functions of dairy cattle as well.…”
Section: Se and Dairy Cattle Healthmentioning
confidence: 98%
“…Several studies have shown a negative correlation that exists between whole blood GPX1 activity and bulk tank milk SCC [44, 76]. Higher blood GPX activity following Se supplementation also was correlated to reduced prevalence of new intramammary infections in pastured heifers [46]. Less is known concerning the role of other selenoproteins in bovine immune and inflammatory responses.…”
Section: Se and Immune Cell Functionsmentioning
confidence: 99%
“…Studies on Se supplementation alone showed that it tended to reduce the prevalence of intramammary infections and decrease the prevalence of quarters with high somatic cell count at calving (Ceballos‐Marquez et al., ). On another study, the authors failed to identify an association between the concentration of Se and the SCC at the level of bulk tanks, although they identified that higher bulk tank Se concentration was associated with a lower risk of being a Staphylococcus aureus positive herd (Ceballos‐Márquez et al., ).…”
Section: Benefits Of Antioxidant Supplementationmentioning
confidence: 99%
“…However, supplementing vitamin E at 3,000 IU/d beginning 2 mo before calving increased blood, liver, milk, and follicular fluid levels of vitamin E in other reports (Bouwstra et al, 2008;Dobbelaar et al, 2010). In addition, Ceballos-Marquez et al (2010) found that supplementing Se to Chilean Holstein-Friesian heifers precalving via a single barium selenite injection or Se yeast at 3 mg/head daily for 45 d increased blood glutathione peroxidase activity and tended to reduce IMI and quarters with high SCC at calving. Kincaid et al (1997) fed weaned calves (6-12 wk of age) starter containing Zn at various concentrations from Zn-Met, Zn-Lys, or ZnO.…”
Section: Vitamins and Mineralsmentioning
confidence: 86%